An investigative study of anxiety, depression and sleep quality in college students after the COVID-19 pandemic - the moderating effect of physical activity - Zhang, Rong; Cheng, Meichao; Zhao, Lingqiang (Journal of Medicine and Health Sciences Research, 2024)
To explore the current situation of anxiety, depression and sleep quality among college students after the COVID-19 pandemic, as well as the moderating effect of physical activity on negative emotions, and to provide a theoretical basis for colleges and universities to formulate corresponding interventions. An online cross-sectional questionnaire survey was carried out by convenience sampling method on 801 college students from China through the General Information Questionnaire (GIQ), Anxiety Self-Rating Scale (ASRS), Depression Self-Rating Scale (DSRS), Pittsburgh Sleep Quality Index Scale (PQIS), and Physical Activity Rating Scale (PARS). Data were analysed using SPSS 25.0 software and Pearson correlation was used to explore the correlations between variables. The scores of anxiety, depression, sleep quality, and physical activity level of the 801 college students included in the study after the Covid-19 pandemic were 37.15, 40.93, 2.9, and 14.44, respectively; and the detection rates of anxiety symptoms, depressive symptoms, and sleep disorders were 41.09%, 42.89%, and 30.82%, respectively. The detection rate of negative emotions was significantly higher in females than in males, and the senior group was significantly higher than the junior group in terms of depression and anxiety symptoms. The amount of physical activity of college students was significantly negatively correlated with anxiety (r=-0.691, P<0.001), depression (r=-0.767, P<0.001), and sleep quality (r=-0.814, P<0.001); anxiety was positively correlated with depression (r=0.622, P<0.001) and sleep quality (r=0.598, P<0.05); and positive correlation between depression and sleep quality (r=0.512, P<0.05). After the Covid-19 pandemic, college students showed different degrees of anxiety, depression and sleep disorders, the appropriate frequency of exercise can effectively improve the negative emotions of college students, and colleges and universities should pay attention to guiding the students and give them enough care and support to improve their mental health status.